2014
DOI: 10.3171/2014.2.peds1392
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative changes in transcranial motor evoked potentials and somatosensory evoked potentials predicting outcome in children with intramedullary spinal cord tumors

Abstract: Object Intraoperative dorsal column mapping, transcranial motor evoked potentials (TcMEPs), and somatosensory evoked potentials (SSEPs) have been used in adults to assist with the resection of intramedullary spinal cord tumors (IMSCTs) and to predict postoperative motor deficits. The authors sought to determine whether changes in MEP and SSEP waveforms would similarly predict postoperative motor deficits in children. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 57 publications
1
48
0
Order By: Relevance
“…In contrast, hemangioblastomas are located posteriorly (Mandigo et al, 2009) and should be removed in an en bloc fashion; debulking of the tumor should be avoided (Brotchi, 2002;Mandigo et al, 2009;Takami et al, 2015). However, previous studies on IONM for IMSCT did not separate tumors according to their specific pathology but instead grouped them together as IMSCT (Kothbauer, 2007;Hyun and Rhim, 2009;Cheng et al, 2014;Choi et al, 2014;Kobayashi et al, 2014).…”
mentioning
confidence: 80%
“…In contrast, hemangioblastomas are located posteriorly (Mandigo et al, 2009) and should be removed in an en bloc fashion; debulking of the tumor should be avoided (Brotchi, 2002;Mandigo et al, 2009;Takami et al, 2015). However, previous studies on IONM for IMSCT did not separate tumors according to their specific pathology but instead grouped them together as IMSCT (Kothbauer, 2007;Hyun and Rhim, 2009;Cheng et al, 2014;Choi et al, 2014;Kobayashi et al, 2014).…”
mentioning
confidence: 80%
“…9,26 A microsurgical alternative to the CO 2 laser is the cavitational ultrasonic surgical aspirator (CUSA) in spinal cord tumor surgery. 4,7 Regarding the bony approach to the spinal cord, various strategies ranging from keyhole approaches (for example, hemilaminectomies) to more extensive multiple-level laminectomies in large ISC were applied in our cohort. Recent approaches focus on nondestructive, minimally invasive strategies if possible to obtain an adequate anatomical overview.…”
Section: Discussionmentioning
confidence: 99%
“…Morota et al reported a MEP sensitivity of 100% in all 3 patients, who showed more than 50% decrease of MEP amplitude resulted in paraplegia at immediate postoperative period [6]. Cheng et al also presented 100% sensitivity of transcranial MEP in all 6 patients with MEP changes out of 12 paediatric patients with intramedullary tumours [7]. And they evaluated SSEP changes and only 3 out of 7 patients with SSEP changes showed postoperative sensory deficit.…”
Section: Predictability Of Mep and Ssep For Postoperative Motor Deficitmentioning
confidence: 99%
“…Later, MEP has played role in intramedullary spinal cord tumour surgery, where motor and sensory pathway could be separately dissected [6,7]. Among spinal tumours, intradural extramedullary (IDEM) and epidural (ED) metastatic spinal tumours are ideal for monitoring surgical manipulation of spinal cord as those tumours are free of both intrinsic pathologic condition of spinal cord and selective spinal cord dissection such as myelotomy.…”
Section: Introductionmentioning
confidence: 99%